Mechanism of Thyrotoxic Periodic Paralysis - Lin, Shih-Hua (American Society of Nephrology, 2012)
The pathogenesis of thyrotoxic periodic paralysis has long been thought related to increased Na(+)–K(+) ATPase activity stimulated by thyroid hormone and/or hyperadrenergic activity and hyperinsulinemia. This mechanism alone, however, cannot adequately explain how hypokalemia occurs during acute attacks or the associated paradoxical depolarization of the resting membrane potential. Recent findings that loss of function mutations of the skeletal muscle-specific inward rectifying K(+) (Kir) channel, Kir2.6, associate with thyrotoxic periodic paralysis provide new insights into how reduced outward K(+) efflux in skeletal muscle, from either channel mutations or inhibition by hormones (adrenalin or insulin), can lead to a vicious cycle of hypokalemia and paradoxical depolarization, which in turn, inactivates Na(+) channels and causes muscle unexcitability and paralysis.